2008
DOI: 10.1002/mar.20257
|View full text |Cite
|
Sign up to set email alerts
|

Comparing leading theoretical models of behavioral predictions and post‐behavior evaluations

Abstract: This study aimed at comparing the predictive power of the Theory of Planned Behavior (TPB), the Model of Goal-Directed Behavior (MGB), and the Extended Model of Goal-Directed Behavior (EMGB) for observed and self-reported behaviors concerning consumer nondurables. More specifically, the three models were compared in terms of their predictive power for intention and for behavioral desire (only MGB and EMGB). Additionally, the validity of four different models for predicting post-behavior evaluations was examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 58 publications
(65 reference statements)
3
28
0
1
Order By: Relevance
“…Perugini and Bagozzi () have also suggested that BD mediates the influence of positive and negative emotions on behavioral intention. Such a mediational role has been confirmed by several studies (see Richetin, Perugini, Adjalia, & Hurling, ).…”
Section: A Psychosocial Theoretical Framework For Investigating Intensupporting
confidence: 61%
“…Perugini and Bagozzi () have also suggested that BD mediates the influence of positive and negative emotions on behavioral intention. Such a mediational role has been confirmed by several studies (see Richetin, Perugini, Adjalia, & Hurling, ).…”
Section: A Psychosocial Theoretical Framework For Investigating Intensupporting
confidence: 61%
“…Consumer behavior tends to be goal‐directed: in other words, the consumer is motivated to purposefully and consciously attain a particular goal (Bagozzi et al., ; Dholakia, ; Richetin, Perugini, Adjali, & Hurling, ). Psychological research contends that individuals cognitively appraise consumption on the consistency of consequences with their expectations (Lazarus, ; Soscia, ).…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…Implementation desire (ID) measures how much an individual is willing to implement certain steps in achieving their desired goals (Richetin, Perugini, Adjali & Hurling, 2008). Several studies that have studied the relationship between implementation desire and implementation intention have found significant positive linkage, but in no-franchise setting (Bagozzi, et al, 2003;Dholakia, et al, 2007;Nadkarni, 2009).…”
Section: Review Of Literaturementioning
confidence: 99%